The effect of ad appeal in influencing attitudes and purchase intentions toward green products - Jiawen, Fan (2020)
Purpose: The purpose of the study is to examine how rational, emotional and mixed appeals influence attitudes and purchase intentions in the advertising. The study also attempts to examine the moderators related to pro-environmental products influencing the relationship between ad appeal and attitudes.